Hospital Anxiety and Depression in the Elderly with Chronic Heart Failure - P Farokhnezhad Afshar; F Bastani; H Haghani; O Valipour (نشریه پرستاری ایران, 2019)
Background & Aims: Evidence suggests that the prevalence of chronic diseases (e.g., coronary heart disease) is on the rise in elderly patients, which is associated with increased psychological complications, such as hospital anxiety and depression. The present study aimed to investigate hospital anxiety and depression in the elderly patients with chronic heart failure in Firooz Abadi Teaching hospital in Tehran, Iran in 2018-2019. Materials & Methods: This cross-sectional study was conducted on 250 hospitalized elderly patients with chronic heart failure, who were selected via continuous sampling in 2019. Data were collected using a demographic questionnaire, the abbreviated mental test score (AMTS) for cognitive assessment, and the hospital anxiety and depression scale (HADS). The data collection tools were completed for each subject via face-to-face interviews with the researcher (15-20 minutes). Data analysis was performed in SPSS version 16 using descriptive and inferential statistics, independent t-test, and analysis of variance (ANOVA) at the significance level of P≤0.05. Results: The majority of the patients (64.8%) were aged 60-74 years, and 52% and 48% of the patients were male and female, respectively. The mean score of anxiety was 1.52±1.14, and the mean score of depression was 2.18±1.51, which indicated the normal levels of hospital anxiety and depression. Significant correlations were observed between hospital anxiety and depression with gender, so that the female elderly patients had significantly higher hospital anxiety and depression scores compared to the male elderly patients (P=0.024). Conclusion: According to the results, hospital anxiety and depression in the elderly patients with chronic heart failure had low levels. Since even low levels of these conditions could disrupt the interactions and care process between healthcare providers and elderly patients, evidence-based data could be used to promote the quality of standard nursing care in the planning of elderly-friendly hospitals by healthcare managers and policymakers.